RISING INCIDENCE OF FATTY LIVER DISEASE IN YOUNG ADULTS: EPIDEMIOLOGY, RISK FACTORS, AND PUBLIC HEALTH IMPLICATIONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Non-alcoholic fatty liver disease (NAFLD), recently rebranded as metabolic dysfunction-associated steatotic liver disease (MASLD), has emerged as one of the most pressing chronic liver conditions affecting the global population. Historically perceived as a disease of middle-aged and older adults with metabolic comorbidities, NAFLD is now increasingly diagnosed in adolescents and young adults aged 15–39 years. This demographic shift represents a significant public health concern, as early-onset hepatic steatosis provides a longer window for disease progression to non-alcoholic steatohepatitis (NASH), cirrhosis, and hepatocellular carcinoma.